Data management at the Oulu cosmic ray station - Poluianov, Stepan; Usoskin, Ilya; Ibragimov, Askar (2021)
With the recent electronics upgrade of Antarctic neutron monitors (NMs) DOMC and DOMB in 2019, the Oulu cosmic ray station (Sodankylä Geophysical Observatory, Finland) receives a significantly larger amount of data than before. This has led to a need for an important upgrade of the configuration of servers working at the station. The new configuration has three types of servers: a web-server, a datamaster server and data acquisition machines. The web-server provides a user interface for services of the station: the main website, the GLE database and other services. The datamaster is the main server, which stores all data in raw files and a database. Data acquisition machines are computers that directly receive data from the instruments and send the files farther to the datamaster server. This work describes technical details of the cosmic ray station setup providing reliable and secure data acquisition, handling and publication.